Increased Expression of the EZH2 Polycomb Group Gene in BMI-1-Positive Neoplastic Cells during Bronchial Carcinogenesis - Breuer, Roderick H J (Neoplasia Press Inc., 2004)
Polycomb group (PcG) genes are responsible for maintenance of cellular identity and contribute to regulation of the cell cycle. Recent studies have identified several PcG genes as oncogenes, and a role for PcG proteins in human oncogenesis is suspected. We investigated the expression of BMI-1 and EZH2 PcG oncogenes in human bronchial squamous cell carcinomas (SCCs) and bronchial premalignant precursor lesions (PLs). Whereas normal bronchial epithelium was associated with widespread expression of BMI-1 in resting EZH2-negative cells, neoplastic cells in lung carcinomas displayed altered expression of both BMI-1 and EZH2. Two patterns of abnormal PcG expression were observed: increased expression of BMI-1 in dividing neoplastic cells of PLs and SCCs, and enhanced expression of EZH2 and Ki-67 in BMI-1-positive cells according to severity of the histopathologic stage. We propose that altered expression of BMI-1 and EZH2 is an early event that precedes high rates of proliferation in lung cancer. Because PcG complexes are normally involved in the maintenance of cell characteristics, abnormal PcG expression may contribute to loss of cell identity.